2020
DOI: 10.1002/ecy.2918
|View full text |Cite
|
Sign up to set email alerts
|

Upwelling buffers climate change impacts on coral reefs of the eastern tropical Pacific

Abstract: Corals of the eastern tropical Pacific live in a marginal and oceanographically dynamic environment. Along the Pacific coast of Panam a, stronger seasonal upwelling in the Gulf of Panam a in the east transitions to weaker upwelling in the Gulf of Chiriqu ı in the west, resulting in complex regional oceanographic conditions that drive differential coral-reef growth. Over millennial timescales, reefs in the Gulf of Chiriqu ı recovered more quickly from climatic disturbances compared with reefs in the Gulf of Pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…The interannual and seasonal water temperature patterns we describe are consistent with a contemporaneous study showing that upwelling in the Gulf of Panama acted as a thermal buffer against increases in temperature during the 2016–2017 El Niño (Randall et al 2020). Our results indicate that as ENSO conditions shifted from a warm phase to a cool phase, wet season and dry season water temperatures declined in the Gulf of Chiriqui.…”
Section: Discussionsupporting
confidence: 89%
“…The interannual and seasonal water temperature patterns we describe are consistent with a contemporaneous study showing that upwelling in the Gulf of Panama acted as a thermal buffer against increases in temperature during the 2016–2017 El Niño (Randall et al 2020). Our results indicate that as ENSO conditions shifted from a warm phase to a cool phase, wet season and dry season water temperatures declined in the Gulf of Chiriqui.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, marginal reefs in the eastern tropical Pacific that experienced strong, seasonal, cold-water upwelling were more vulnerable to millennial-scale climatic perturbations during the Holocene than reefs with more stable annual temperatures (i.e., in the Gulf of Panama 8 and the Gulf of Papagayo, Costa Rica 13 ). Whereas moderate levels of thermal variability can increase the resilience of reefs to modern climatic extremes 21 , 22 , 70 , 71 , these studies of Holocene reef development suggest that in marginal habitats, where variability in the physical environment is especially high, periodic disturbances may be more likely to push reefs past critical environmental thresholds for continued survival and reef-building 9 , 11 , 22 , 71 .…”
Section: Introductionmentioning
confidence: 90%
“…In environments where thermal conditions are marginal, even minor cooling has the potential to suppress or even shut down reef-building by species that evolved in the tropics 4,9,11,14,17,18 . Whereas a number of recent studies have suggested that marginal environments-highlatitude habitats, mesophotic reefs, and locations with elevated turbidity or upwelling-could serve as refugia from warming for thermally sensitive coral taxa [19][20][21][22] , most of these ecosystems do not support reef accretion at present 20 . An important question, therefore, is whether and how the response of marginal reefs to climatic trends in the past can be used to project the future development of today's degrading reef ecosystems 6,7 in response to anthropogenic warming trends and the impact of those recent trends on both warm and cold thermal extremes.…”
mentioning
confidence: 99%
“…Thus, fronts can modify the wind field and subsequently influence regional circulation (De Szoeke et al., 2007; Xie et al., 1998). A better knowledge of frontal variability in the eastern Pacific Ocean could improve the understanding of ecosystem variability, air‐sea coupling and their underlying dynamics at both regional and global scales (Bakun et al., 2015; Randall et al., 2019).…”
Section: Introductionmentioning
confidence: 99%